Arecibo and FAST timing follow-up of 12 millisecond pulsars discovered in Commensal Radio Astronomy FAST Survey. Issue 2 (13th July 2022) - Miao, C C; Zhu, W W; Li, D; Freire, P C C; Niu, J R; Wang, P; Yuan, J P; Xue, M Y; Cameron, A D; Champion, D J; Cruces, M; Chen, Y T; et al.
ABSTRACT: We report the phase-connected timing ephemeris, polarization pulse profiles, Faraday rotation measurements, and Rotating-Vector-Model (RVM) fitting results of 12 millisecond pulsars (MSPs) discovered with the Five-hundred-meter Aperture Spherical radio Telescope (FAST) in the Commensal Radio Astronomy FAST survey (CRAFTS). The timing campaigns were carried out with FAST and Arecibo over 3 yr. 11 of the 12 pulsars are in neutron star–white dwarf binary systems, with orbital periods between 2.4 and 100 d. 10 of them have spin periods, companion masses, and orbital eccentricities that are consistent with the theoretical expectations for MSP–Helium white dwarf (He WD) systems. The last binary pulsar (PSR J1912−0952) has a significantly smaller spin frequency and a smaller companion mass, the latter could be caused by a low orbital inclination for the system. Its orbital period of 29 d is well within the range of orbital periods where some MSP–He WD systems have shown anomalous eccentricities, however, the eccentricity of PSR J1912−0952 is typical of what one finds for the remaining MSP–He WD systems.